Hormonal, follicular and endometrial dynamics in letrozole-treated versus natural cycles in patients undergoing controlled ovarian stimulation - Brunengraber Lisa N; Hussein Mostafa; Mousa Noha; Abdelaleem Mahmoud A; Bedaiwy Mohamed A; Casper Robert F (BMC, 2011)
Abstract The objective of this study was to compare letrozole-stimulated cycles to natural cycles in 208 patients undergoing intrauterine insemination (IUI) between July of 2004 and January of 2007. Group I (n = 47) received cycle monitoring only (natural group), Group II (n = 125) received letrozole 2.5 mg/day on cycle days three to seven, and Group III (n = 36) received letrozole 5 mg/day on cycle days three to seven. There were no differences between the groups in endometrial thickness or P4 on the day of hCG. Estradiol levels had higher variation in the second half of the follicular phase in both letrozole-treated groups compared to the control group. Estradiol per preovulatory follicle was similar in both letrozole cycles to that observed in the natural cycles. LH was lower on the day of hCG administration in the letrozole 2.5 mg/day group vs. the natural group. In summary, letrozole results in some minor changes in follicular, hormonal and endometrial dynamics compared to natural cycles. Increased folliculogenesis and pregnancy rates were observed in the letrozole-treated groups compared to the natural group. These findings need to be confirmed in larger, prospective studies.